AN ANALYSIS OF INDONESIAN-ENGLISH CODE MIXING USED BY MALE AND FEMALE BROADCASTERS AT SWARAUNIB RADIO STATION - Novri Ferdiansyah; Arasuli Arasuli; Alamsyah Harahap; Mulyadi (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2023)
The objectives of this research were to find out 1).  the most common types of code-mixing used by male and female broadcasters at Swaraunib radio station 2).to find out the reasons for using Indonesian - English code-mixing by male and female broadcasters at Swaraunib Radio station. The subjects of this study were 6 broadcasters at Swaraunib radio station, with 3 male and 3 female broadcasters. The design of this research was descriptive, used quantitative as well as qualitative data. The result showed that there were three types of code-mixing proposed by Hoffman.  The results for male broadcasters showed that there were 282 (87%) cases of intra-sentential code mixing, 31 (9,6%) cases of intra-lexical code mixing, and 11 (3,4%) involvement in a change of pronunciation. Meanwhile, the results for female broadcasters showed that there were 357 (89,9%) cases of intra-sentential code mixing, 28 (7,1%) cases of intra-lexical code mixing, and 12 (3%) involvement in a change of pronunciation. While for reasons of using code-mixing, female broadcasters and male broadcasters both used seven reasons from Hoffman's theory. The reasons were talking about particular topic, quoting somebody else, being emphatic about something, interjection, repetition used for clarification, and clarifying the speech content for the interlocutor, and expressing group identity and solidarity In addition, female broadcasters using code-mixing tended to be more conscious and intentional than male broadcasters, and female broadcasters were more expressive than male broadcasters in the use of code-mixing. In conclusion, although the most common types and reasons for using code mixing between male and female broadcasters were similar, there were still differences that were influenced by gender factors. However, code mixing can be used to create a good and interesting communication, especially in broadcasting media.